Pelatihan Pembuatan Soal Berpikir Kreatif untuk Mengembangkan HOTS Siswa bagi Guru Matematika SMP - Soraya Djamilah; Iin Ariyanti (LPMP Imperium, 2020)
This activity aims to increase the understanding and knowledge of mathematics teachers in making creative thinking questions to develop student's HOTS. So that the teacher as the frontline in education is able to develop a student’s creative thinking skills in learning and assessment of mathematics. The method used in this activity is in the form of a short training in making creative thinking questions to develop student’s HOTS. Participants are given training in the form of presentations, demonstrations about creative thinking, and discussions. Participants in the activity are teachers who are members of Musyawarah Guru Mata Pelajaran (MGMP) Mathematics of Junior High School in Kabupaten Banjar engaged very well and enthusiastically during the activity. Keywords: Creative thinking, HOTS, mathematics